2020
DOI: 10.1002/ece3.6383
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the concept of indicator populations derived from parentage‐based tagging in a large‐scale coho salmon application in British Columbia, Canada

Abstract: For Pacific salmon, the key fisheries management goal in British Columbia (BC) is to maintain and restore healthy and diverse Pacific salmon populations, making conservation of salmon biodiversity the highest priority for resource management decision‐making. Salmon status assessments are often conducted on coded‐wire‐tagged subsets of indicator populations based on assumptions of little differentiation within or among proximal populations. In the current study of southern BC coho salmon (Oncorhynchus kisutch) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…An additional caveat to our analysis is its dependence on data from hatchery-origin fish, which dominate CWT data, to make inferences about stocks consisting of a composite of hatchery-and natural-origin fish. Although Beacham et al (2020) found finescale differences in the distributions of geographically proximate coho salmon (O. kisutch) populations, they noted that Weitkamp and Neely (2002) did not find differences between hatcheryand natural-origin coho salmon distributions at a resolution more comparable to our study. Similarly, generally minor differences have been found between the ocean distributions of naturalversus hatchery-origin Chinook salmon when such comparisons are possible Sharma & Quinn, 2012;Weitkamp, 2010).…”
Section: Discussioncontrasting
confidence: 63%
“…An additional caveat to our analysis is its dependence on data from hatchery-origin fish, which dominate CWT data, to make inferences about stocks consisting of a composite of hatchery-and natural-origin fish. Although Beacham et al (2020) found finescale differences in the distributions of geographically proximate coho salmon (O. kisutch) populations, they noted that Weitkamp and Neely (2002) did not find differences between hatcheryand natural-origin coho salmon distributions at a resolution more comparable to our study. Similarly, generally minor differences have been found between the ocean distributions of naturalversus hatchery-origin Chinook salmon when such comparisons are possible Sharma & Quinn, 2012;Weitkamp, 2010).…”
Section: Discussioncontrasting
confidence: 63%
“…2013; J. E. Hess et al 2016; Beacham et al 2017), including the detection of stray fish confirmed with CWT recoveries (Beacham et al 2017). Studies using PBT have estimated stock‐specific abundances (J. E. Hess et al 2016; Beacham et al 2020), detected thermal refuge utilization during periods of increased water temperatures (M. A. Hess et al 2016), and identified the proportion of hatchery fish on spawning grounds (Hinrichsen et al 2016). Hatchery‐marked fish can be visually assessed for age, where it is generally easy to discriminate between age‐3 fish and older fish based on length, but overlapping lengths often exist for ages 4 and above.…”
mentioning
confidence: 99%
“…Harvest levels for some yearling populations are a considerable frac- This is an important point because the basic ecological models used to inform the Environmental Impact Statements (EIS) for many ESAlisted Columbia River salmon stocks are calibrated using PIT tagbased SAR estimates (McCann et al, 2018;Zabel et al, 2008). The use of modern parentage-based genetic stock ID methods (Beacham et al, 2020;Freshwater et al, 2016;Hess et al, 2011;Matala et al, 2011;Satterthwaite et al, 2014) may allow apportioning harvest from the various fisheries to source populations with sufficient precision to be useful for survival analysis in the Columbia in the future. However, whether these methods can provide sufficient resolution for past harvest rate estimates to be incorporated into SAR estimate is unclear.…”
Section: Con Clus Ionsmentioning
confidence: 99%